Land cover conversion and land use change combine to reduce grazing. Issue 1 (2nd January 2022) - Shapero, Matthew; Siegel, Katherine; Gallo, John A.; Brice, Justin; Butsic, Van
ABSTRACT: Land cover and land use changes cause global environmental degradation yet changes in cover may have different impacts than changes in use. Here, we examine changes in land cover (rangeland conversion to vineyard) and land use (assocaited grazing loss on proximate rangelands) in Santa Barbara County, USA, between 1984 and 2019 paying attention to (1) instances where grazing was removed and (2) the effectiveness of local policies in keeping grazing active. We found that 13% of rangeland parcels converted to vineyards, and that 69% of these properties ceased grazing, even though 92% of the rangeland parcels in our analysis that converted to vineyards still had over 100 acres (40ha) that could be grazed. Statistical models showed that land use policy did not have a significant impact on these changes. Our results show the importance of distinguishing between land use and land cover to understand social and natural system changes.